Legal Protection for Micro, Small, and Medium Enterprises (MSMEs) in Receiving Capital Assistance from Venture Capital Companies - Shri Hardjuno Wiwoho; Azis Budianto (Return : Study of Management, Economic and Bussines, 2024)
The study discusses the responsibilities of venture capital companies in the context of delays in disbursing capital assistance and its impact on Micro, Small, and Medium Enterprises (MSMEs). The main focus is on the problem of default that occurs when venture capital companies fail to fulfill their obligations to disburse capital on schedule, resulting in financial losses and obstacles to business development for MSMEs. This study proposes legal reforms to improve regulations and enforcement related to venture capital company responsibilities, including setting disbursement deadlines, MSME protection mechanisms, and increasing accountability. The empirical normative research uses a combined method between legislative, case, and analytical approaches to explore and analyze legal issues comprehensively. The research finds that MSMEs engage in profit-sharing schemes with venture capital firms. In this arrangement, the venture capital company offers funds to a legal entity partner company, and the partner company reimburses the funds with predetermined rewards. These agreements are governed by the contract law provisions of the Civil Code and are updated by the Ministry of Finance Regulation. It emphasizes the significance of venture capital in addressing funding shortages for small businesses. These reforms are expected to reduce the risk of delays, ensure fair compensation for MSMEs, and support more sustainable business growth.